Strategi monitoring kepatuhan penggunaan antiretroviral pre-exposure prophilaxis pada pasangan serodiscordant - Ni Kadek Diah Purnamayanti; Nurma Yuni Pari Usemahu; Fatih Haris M; Marina Kristi Layun R (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Monitoring strategy of antiretroviral pre-exposure prophylaxis adherence among serodiscordant couple Antiretroviral pre-exposure prophylaxis (PrEP) has been recommended as HIV prevention but poor medical adherence can cause suboptimal therapy. This study explored the strategies of monitoring PrEP adherence among the serodiscordant couples. This systematic review based on 4 data bases (Scopus, Pubmed, Ebsco and Sage Journal), included clinical trial studies articles between 2013-2018, in English, and available in full-text. Papers, which not met the inclusion criteria, will be excluded. Keywords used in this study are ‘serodiscordant couple’ AND ‘method’ OR ‘strategy’ OR ‘approach’ AND ‘pre-exposure prophylaxis intention’ OR ‘pre-exposure prophylaxis adherence’. This study discovered various strategies applied based on the type of delivering process, the variance of dose, and variance of preference of the couple. Preference of PrEP dose and type of application related to heterosexual or homosexual orientation and their social commitment. The paper explains the advantage of M-health and biomarker level monitoring.